Influence of empowering and disempowering motivational climates on academic self-concept amongst STEM, social studies, language, and physical education pre-service teachers: a test of basic psychological needs. - Granero-Gallegos, Antonio; Baena Extremera, Antonio; Ortiz Camacho, María del Mar; Burgueño, Rafael (Taylor & Francis, 2023)
ABSTRACT Guided by the bright and dark side described in Self-Determination Theory, and following hierarchical and integrative conceptualisation of motivational climates, the primary objective of this research was to test the predictive relationships between pre-service teachers’ perceptions of educator-created (dis-)empowering climates and need-based and novelty-based experiences with their academic self-concept. Bearing in mind that the pre-service teachers’ academic self-concept might vary depending on the knowledge domain, a secondary objective was to test invariance in the predictive model across the four knowledge domains (i.e. STEM, social studies, language, and physical education). The convenience sample included 1,410 pre-service secondary teachers (40.30% men; Mage=23.85; SDage= 5.13; domain: 23.2% STEM, 24.8% social studies, 30.5% language, and 21.4% physical education) who participated in this cross-sectional study. The results from the structural equation modelling showed positive relationships between an educator-created empowering climate and need and novelty satisfaction, and negative relationships with need and novelty frustration. A disempowering climate was positively associated with need and novelty frustration, and negatively related to novelty satisfaction. Need satisfaction and novelty satisfaction were positively associated with academic self-concept, while need frustration and novelty frustration were associated negatively. The paths were invariant across the knowledge domains of STEM, social studies, language, and physical education. The results show that, regardless of the knowledge domain, the educator-created motivational climate represents a differential social-contextual factor explaining the need-based and novelty-based experiences, and academic self-concept of pre-service teachers throughout their initial teacher education programme.
https://openpolicyfinder.jisc.ac.uk/id/publication/5202
Keywords: Profesores de educación física - Formación profesional; Estudiantes - Psicología; Social environment; Basic psychological needs; Need for novelty; Cognitive outcomes; Student teacher